Pemeriksaan Kadar HbCO Pada Relawan Pengatur Jalur Putar Balik Di Jalan Menggunakan Metode Spektrofotometer Uv-Vis - Ardani, Rifky (Jurnal Sains dan Teknologi Laboratorium Medik, 2023)
The work of volunteers managing the U-Turn Route is very vulnerable to exposure to carbon monoxide, if it is inhaled by the body it will become CarboxyHemoglobin (HbCO). The aim of this research is to determine the levels of HbCO in volunteers' blood which regulates the U-turn pathway. The research population was 8 male people and the samples were veins. The results of this study showed that the lowest average HbCO level in the respondents' blood was 4.56% and the highest was 8.10%. Based on the age of respondents, 20-35 years old had an average level of 7.1%, aged 35-45 years had an average level of 5.8%. Based on work experience of more than 1 year, the average level is 6.2%, work experience of less than 1 year has an average level of 6.5%. Based on working time of 0-3 hours, it has an average level of 7.1%, working time of 4-7 hours has an average level of 5.6%. This research uses the Shapiro Wilk test and hypothesis testing using the correlation test with a significant value = α < 0.05. and obtained significant results, namely 100% abnormal.